A novel hyaluronidase produced by Bacillus sp. A50. - Xueping Guo; Yanli Shi; Juzheng Sheng; Fengshan Wang (PLoS ONE, 2014)
Hyaluronidases are a family of enzymes that degrade hyaluronic acid (hyaluronan, HA) and widely used in many fields. A hyaluronidase producing bacteria strain was screened from the air. 16S ribosomal DNA (16S rDNA) analysis indicated that the strain belonged to the genus Bacillus, and the strain was named as Bacillus sp. A50. This is the first report of a hyaluronidase from Bacillus, which yields unsaturated oligosaccharides as product like other microbial hyaluronate lyases. Under optimized conditions, the yield of hyaluronidase from Bacillus sp. A50 could reach up to 1.5×10(4) U/mL, suggesting that strain A50 is a good producer of hyaluronidase. The hyaluronidase (HAase-B) was isolated and purified from the bacterial culture, with a specific activity of 1.02×10(6) U/mg protein and a yield of 25.38%. The optimal temperature and pH of HAase-B were 44°C and pH 6.5, respectively. It was stable at pH 5-6 and at a temperature lower than 45°C. The enzymatic activity could be enhanced by Ca2+, Mg2+, or Ni2+, and inhibited by Zn2+, Cu2+, EDTA, ethylene glycol tetraacetic acid (EGTA), deferoxamine mesylate salt (DFO), triton X-100, Tween 80, or SDS at different levels. Kinetic measurements of HAase-B towards HA gave a Michaelis constant (Km) of 0.02 mg/mL, and a maximum velocity (Vmax) of 0.27 A232/min. HAase-B also showed activity towards chondroitin sulfate A (CSA) with the kinetic parameters, Km and Vmax, 12.30 mg/mL and 0.20 A232/min respectively. Meanwhile, according to the sequences of genomic DNA and HAase-B's part peptides, a 3,324-bp gene encoding HAase-B was obtained.